2012 – The year when BAOMS and its officers prevented closure of all UK shortened medical and dental courses. Issue 10 (December 2020) - Magennis, P.; Begley, A.; Martin, I.C.; Hutchison, I.
Abstract: In Spring 2011 the Department of Health (DH) received a request to review European Union Directive 2005/36 EU – the directive relating to the recognition of professional qualifications. The Department of Health lawyer raised concerns that the existing shortened dental courses may be in breach of EU law. There were three shortened dental courses in the UK: 4 year graduate entry courses in Liverpool/Peninsula and 3-year Dental Programme for Medical Graduates (DPMG) in Kings, London. During the summer the General Dental Council (GDC) was made aware of these concerns. In autumn 2011 the Chief Dental Officer for England with the GDC, told the Dental Deans' Council (DDC) that shortened dental courses were illegal. On 12th Jan 2012 students on the DPMG were told that they would have to complete a full 5-year dental degree. The GDC said that this interpretation of EU law would also impact on shortened medical courses. In view of the potentially enormous impact that this would have on OMFS training, BAOMS engaged all the resources it could and by assembling legal opinions including written contributions from Sir David Edward, whose opinion was being misinterpreted by the GDC and DH, and by sharing these resources with all the stakeholders, BAOMS was able to preserve shortened dental and medical courses. Now that the UK has left the European Union, negotiations around mutual recognition of qualifications may mean this issue will resurface. We should remain vigilant.